Processing and characterization of oxygen eletcrode and electrolyte in reversible solid oxide fuel cells - Gómez González, Sergio Yesid (2015)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Ciência e Engenharia de Materiais, Florianópolis, 2015.